The Evolution of the Medical School Deanship: From Patriarch to CEO to System Dean - Schieffler, Danny A (Perm J, 2016)
Medical school deanship in the US has evolved during the past 200 years as the complexity of the US health care system has evolved. With the introduction of Medicare and Medicaid and the growth of the National Institutes of Health, the 19th-century and first half of the 20th-century role of the medical school dean as guild master transformed into that of resource allocator as faculty practice plans grew in scope and grew as an important source of medical school and university revenue. By 2000, the role of the medical school dean had transformed into that of CEO, with the dean having control over school mission and strategy, faculty practice plans, education, research dollars, and philanthropy. An alternative path to the Dean/CEO model has developed—the System Dean, who functions as a team player within a broader health system that determines the mission for the medical school and the related clinical enterprise. In this paper, the authors discuss the evolution of the medical school dean with respect to scope of authority and role within the health care system.